Towards Interdisciplinarity in the Arab World: The Need for Interdisciplinary Studies in the Nascent Saudi Universities - Abdelmagid Abdelrahman Awadelkarim (International Journal of Social Sciences & Educational Studies, 2019)
Interdisciplinary studies/sciences are currently flourishing in numberless Western universities. There are currently, a variety of interdisciplinary research centres, programmes and departments, in many Western universities (sometimes even colleges as in the case of University of British Columbia in Canada). International conferences and special magazines are presently being dedicated to these issues and trends all over the world. By way of contrast, the Arab world, with the exception of very few cases, this tendency is yet to be known, let alone be introduced. It would, therefore, be immensely imperative for the nascent universities, Majmaah university included, to introduce interdisciplinary studies in their undergraduate/postgraduate programmes/plans. It is here that the nascent universities in the Arab world can markedly excel by exploring new horizons, as well as by probing a largely virgin space in education and research. In this way, they can get more competitive in an increasingly tough and pressing labour market, hence can considerably contribute to the knowledge economy of today's time. This paper argues for the need to incorporate interdisciplinary studies/sciences and interdisciplinarity, into the programmes of Arab universities, in general, and the newly established Saudi ones, to be more specific (Majmaah). Data were collected via an array of mixed methods. Chiefly, group discussions and interviews with top managers, high-ranking administrators, educationalists, scholars and pundits from all walks of academia were exploited in the study. Analysis primarily drew on an integration of both qualitative and quantative methods (noting that much of the data required in this study is of qualitative nature, and that much more recent social/human sciences research has importantly disclosed a special inclination towards qualitative data gathering and analysis). Results largely suggest not only the need for adopting and introducing interdisciplinary studies and interdisciplinarity in Majma'ah university, but also, generalizably in the rest of the other newly-established universities/colleges and Arab academia, at large.